Sales Application Using Point of Sales System Method in Coffee Shop Management System - Nurlianti; Ade Hastuty; Mughaffir Yunus; Marlina; Andi Wafiah (Jurnal Vokasi Teknik Informatika, 2026)
The development of information technology requires businesses to shift from manual systems to more efficient digital management. However, Mentuangin Coffee still runs sales processes and reports manually, making them prone to errors, delays in data processing, and difficulties in monitoring stock. This condition indicates the need for an integrated sales system that can support operational activities more accurately and structurally. This study aims to design and develop a sales application based on a Point of Sales (POS) system using the PHP programming language as a solution to automate transaction processes, inventory management, and sales reporting. The research methods used include needs analysis, an object-oriented approach, application implementation, and testing using the Black Box method to ensure all functions run according to specifications. The results show that the developed application is able to process transactions, improve recording accuracy, and generate reports in real time